Applications of Whey Extract and Cpp-Acp in Email Surface Towards Enamel Surface Hardness After Extracoronal Bleaching - Irfan Dwiandhono; Dian Noviyanti Agus Imam; Afiatul Mukaromah (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2019)
Teeth have an aesthetic value because teeth which are clean, neat and white can increase self confidence. Staining or dental discoloration can disrupt the appearance and cause discomfort. The most common type of discoloration is extrinsic discoloration. Treatment that can be done to overcome extrinsic discoloration is extracoronal bleaching. One way to avoid the extracoronal bleaching side effects is application of remineralization materials. The recommended remineralization materials for post-bleaching are fluoride and phospho peptide-amorphous calcium phosphate (CPP-ACP). This research aims to know the effect of whey extract application and CPP-ACP on tooth enamel hardness after extracoronal bleaching. Experimental laboratory with pre- and post-test control design was performed on 24 first maxillary premolar which devided into 3 groups. On group I, specimens were immersed in artificial saliva. Specimen in group II were immersed in whey extract meanwhile specimens were immersed in CPP-ACP on group III. Whey extract and CPP-ACP immersions were conducted 10 minutes every 12 hours for 15 days. The enamel surface roughness test was performed twice, after extracoronal bleaching treatment and after 15 days remineralization agent application. This study result indicated significant differences between group I and group II and group III (p0,05), but there was no significant difference between group II and group III (p0,05). This study showed the enamel surface hardness after whey extract application is higher than CPP-ACP but difference was not significant statistically